The Importance of Nanopharmaceuticals and Nanomedicines Applications and Properties: A Current Review - Jaafar, Hawraz Jawdat (Technium BioChemMed, 2023)
Nanotechnology is recognized as a new and rapidly developing field in the pharmaceutical and medical fields. The breakthroughs in nanoscience are developing in almost every field of science, and at the same time, nanotechnologies make life easier in terms of science in the modern era. Nanoscience and nanotechnology are developing fields of study that involve structures, devices, and systems with innovative features and functionalities as a result of the arrangement of their atoms on the 1-100 nm scale. This area became the subject of increasing public awareness and debate in the early 2000s. Nanotechnology contributes to nearly every field of science, including physics, materials science, chemistry, biology, computer science, and engineering. Especially in recent years, nanotechnologies have been applied to human health with promising results, especially in the field of cancer therapy. Moreover, in recent years, nanotechnology has become a widely used technology in a wide range of medical and pharmaceutical applications. Drug-delivery systems based on nanoparticle technology have the potential to launch an industrial revolution that might serve as a watershed moment for future pharmaceutical industries. The main aims of developing nanoparticles as a delivery system are to improve bioavailability by increasing solubility and dissolution rate, to target the drug to specific organs, and to control the drug release rate. To fully understand the nature of nanotechnology, it is useful to review the history of discoveries that led to the current understanding of this science. This review summarizes the progress and key principles of nanomedicine, nanopharmaceuticals, nanoscience, and nanotechnology, and also highlights the pre-modern and modern historical ages of discoveries and historical milestones of nanotechnology and nanomedicines.